An evaluation of the teaching function of the community health nurse with clients on breast self-examination in family planning clinics in Bloemfontein - Nowlan, G. P. (University of the Free State, 1979)
This study was done to investigate the teaching function of the nurse on breast self-examination and breast cancer as breast cancer death rates are rising yearly. Chapter 1 included an introduction into the problem of breast cancer. The problem of breast cancer is reviewed briefly including such aspects as incidence of breast cancer, factors which influence the health practice of breast self-examination and factors influencing the health education of clients. The objectives of the study we re to determine whe t.her the community health nurse taught breast self-examination to her clients and whether increased factual knowledge about breast cancer led to a positive attitude, towards preventive action. Limitations of the study were that only white clients, mainly in the younger age groups were contacted for the study due to the type of clinic used, viz. family planning clinics. The research method made use of experimental and descriptive methods while a literature study and questioning were the techniques used for the gathering of data. The study comprised of two parts - A pretest was administered at the family planning clinic where a demonstration on breast examination was given together with pamphlets from the National Cancer Association. After three months: the posttest was administered by telephone and personal contact. These two results were then compared with each other to indicate an improvement in breast self-examina.tion practice. Chapter 2 outlined the problem of breast cancer and its implications in more detail. Statistics showed an increase in deaths from breast cancer. Attitudes such as fear and ignorance of breast cancer and lack of confidence in their ability to detect breast lumps seemed to be the most common reason why most women did not practice breast self-examination. The importance of health education on breast cancer was pointed out in the light of what different authorities had to say about health education. The role of the nurse in health education on breast, cancer and breast self-examination was also clearly set out. Chapter 3 includes both objective observation to be made by the nurse during her examination of the breasts and subjective observations to be taught to the client together with a motivation for regular breast self-examination. In this chapter there is also a short classification of morphological types of breast cancer and prognostic variables which influence the survival rate. Chapter 4 is an analysis of the research data. Results from the pretest on factual knowledge were compared with those of the posttest which revealed an improvement of knowledge on breast cancer in all the cases. Some misconceptions about the causes of breast cancer were held even after the teaching programme. These included beliefs that contraceptive pills and being hit on the breast were responsible for breast cancer. In the section on beliefs about breast cancer it was found that there was an improvement in perceived benefit of breast self-examination and more respondents realized that they too were more susceptible to the threat of breast cancer. Attitudes on the whole became more positive towards breast cancer. Regular breast self-examination practice improved, but not in all cases on a monthly basis as was required of them. Also it was shown that not only those with high beliefs in perceived benefit of breast self-examination were the ones to practice breast self-examination regularly, but also those with moderate belief had a high rate of compliance. Some respondents with high beliefs in perceived benefit did not practice breast self-examination at all. The main reasons for non-compliance seemed to be forgetfulness and an unwillingness to think about breast cancer. Those respondents who were unwilling to think about breast cancer fell mainly in the younger age groups and who mostly took the attitude that they could think about breast cancer later in life, Chapter 5 includes some factors which possibly had an effect on the study results. Briefly, these were lack of time on the part of the respondents and failure by the nurses to stress the importance of breast self-examination strongly enough. It was recommended that older women should receive more attention in teaching programmes as they are the ones in the high risk group, and that demonstrations should be given to all women on a group and a one-to-one basis. Further studies are required in the field of teaching techniques of breast self-examination to determine the best and most effective method to ensure compliance. Posttesting should be continued over a period of two years so that a more accurate picture could be gained of compliance with this health practice.
Dissertation (M.Soc.Sc. (Community Health Nursing))--University of the Free State, 1979
Keywords: Health education; Breast -- Cancer; Breast -- Diseases; Breast -- Cancer -- Diagnosis; Cancer; Breast -- Examination